1990
DOI: 10.1111/j.1432-1033.1990.tb19391.x
|View full text |Cite
|
Sign up to set email alerts
|

A study on the regulation of N‐glycoloylneuraminic acid biosynthesis and utilization in rat and mouse liver

Abstract: The relative contribution of N-glycoloyl-P-D-neuraminic acid (NeuSGc) to total sialic acids expressed in mouse and rat liver glycoconjugates was found to be 95% and 11%, respectively. This considerable difference in sialic acid composition made these two tissues suitable models for a comparative investigation into the regulation of NeuSGc biosynthesis and utilization.An examination of the CMP-glycoside specificity of Golgi-associated sialyltransferases using CMP-N-acetylp-D-neuraminic acid (CMP-NeuSAc) and CMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…In our own prior work (16) we concluded that CMP-Neu5Gc and CMP-Neu5Ac could be taken up by Golgi vesicles and incorporated into the endogenous glycoproteins at an approximately equal rate. Similar observations were made by Lepers et al (20,21) in rat and mouse liver Golgi. Thus, we could ask whether Neu5Gc and Neu5Ac are taken up and incorporated via the same pathways by doing competition experiments in Caco-2 and human normal fibroblast cells.…”
Section: Fig 3 Uptake Of Free Neu5gc Is Not Specific For Human Cellssupporting
confidence: 90%
“…In our own prior work (16) we concluded that CMP-Neu5Gc and CMP-Neu5Ac could be taken up by Golgi vesicles and incorporated into the endogenous glycoproteins at an approximately equal rate. Similar observations were made by Lepers et al (20,21) in rat and mouse liver Golgi. Thus, we could ask whether Neu5Gc and Neu5Ac are taken up and incorporated via the same pathways by doing competition experiments in Caco-2 and human normal fibroblast cells.…”
Section: Fig 3 Uptake Of Free Neu5gc Is Not Specific For Human Cellssupporting
confidence: 90%
“…NeuGc is one of the abundant derivatives of sialic acid and is expressed in most mammals. For example, NeuGc comprises 95 and 11% of total sialic acids expressed in mouse and rat liver glycoconjugates, respectively (16). Almost all sialic acid in rat thymus CD45 and Thy-1 is NeuGc (25).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the major mechanism for biosynthesis of NeuGc is hydroxylation of CMP-NeuAc (13)(14)(15)(16). Therefore, the activity of CMP-NeuAc hydroxylase plays a key role in the regulation of NeuGc expression in glycoconjugates.…”
mentioning
confidence: 99%
“…This conversion from CMP-Neu5Ac to CMP-Neu5Gc in the cytosol is catalyzed by CMP-Neu5Ac hydroxylase (Cmah) (25,26). The ratio of the cytosolic CMP-Neu5Ac and CMP-Neu5Gc pool likely determines the Neu5Ac/Neu5Gc ratio in cell surface sialoglycans, because the Golgi CMP-sialic acid transporter and sialyltransferases can utilize both CMP-Neu5Ac and CMPNeu5Gc as substrates without strong preferences (27)(28)(29). Because of the differential regulation of Cmah expression, the ratio of these two major sialic acids varies markedly among different tissues in different animal species except for certain species like humans that have an inactive CMAH gene (CMAHP) and lack endogenous Neu5Gc expression throughout the body.…”
mentioning
confidence: 99%